Design of Device for Detecting Alcohol Content in Perfume Using the MQ-3 Sensor: Case Studies on Various Perfume Brands - Udi Renaldi; Mudofar Baehaqi; Deni Wachyudin (Mestro, 2021)
Perfume oils have become a popular consumer product worldwide. The use of perfume oil is not only related to a personal need to smell good, but is also part of one's culture and identity. One of the main components in perfume oil is alcohol, which serves as a solvent to transport and evaporate fragrances. Alcohol is a common ingredient used in the manufacture of perfumes and can affect the quality and characteristics of the fragrance. Therefore, it is important to monitor the level of alcohol in perfume. In this research, we designed and developed a device for detecting alcohol content in perfume using the MQ-3 sensor. The main objective of this research is to obtain accurate data on alcohol content in various perfume brands on the market. This research consists of several stages. First, we selected and collected various perfume brands as samples. Then, we designed an electronic circuit consisting of an MQ-3 sensor, an Arduino microcontroller, and an LCD brightness module as a display interface. The results showed that the designed detector was able to measure the alcohol content in perfume with sufficient accuracy. In our case study, we found variations in alcohol content between different perfume brands. The result of the measurement is that the farther the measurement distance, the smaller the value of the sensor reading. Every vulnerable distance of 1cm has a difference of 45% - 50%.